Mold-glass interface adhesion mechanisms in precision glass molding - Zhao, Hanhan; Zhang, Liangchi (Advanced Optical Technologies, 2025)
Precision glass molding (PGM) enables high-accuracy, efficient production of complex optical components, yet interfacial adhesion between mold and glass surfaces remains a significant barrier, impacting both quality and mold durability. This review comprehensively examines the factors influencing adhesion behavior, including the roles of material selection, surface wettability, process parameters, and thermodynamic principles in defining interfacial performance. Through a detailed analysis of anti-adhesion materials and optimized process strategies, such as controlled temperature, pressure, and atmospheric conditions, this work elucidates mechanisms that mitigate adhesion and extend mold life. Thermodynamic modeling, including work of adhesion calculations, provides a quantitative foundation for predicting interfacial behavior, offering guidance for material and process optimization in PGM applications. The findings provide a multi-dimensional framework for addressing adhesion challenges in PGM, setting the stage for enhanced efficiency and quality in precision optics manufacturing.